2017
DOI: 10.1017/s0952523817000098
|View full text |Cite
|
Sign up to set email alerts
|

Not a one-trick pony: Diverse connectivity and functions of the rodent lateral geniculate complex

Abstract: Often mislabeled as a simple relay of sensory information, the thalamus is a complicated structure with diverse functions. This diversity is exemplified by roles visual thalamus plays in processing and transmitting light-derived stimuli. Such light-derived signals are transmitted to the thalamus by retinal ganglion cells (RGCs), the sole projection neurons of the retina. Axons from RGCs innervate more than ten distinct nuclei within thalamus, including those of the lateral geniculate complex. Nuclei within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(110 citation statements)
references
References 166 publications
1
109
0
Order By: Relevance
“…Recent advances in transgenic labeling of individual RGC subtypes has revealed the precise architecture of these hidden laminae of subtype-specific retinal arbors in dLGN (Cruz-Martín et al 2014;Huberman et al 2008;Huberman et al 2009;Kay et al 2011;Kim et al 2010;Kim et al 2008;Martersteck et al 2017;Rivlin-Etzion et al 2011;Kerschensteiner & Guido 2017;Monavarfeshani et al 2017). In this study, however, we identified a different kind of 'hidden laminae' within vLGN.…”
Section: Different Types Of Hidden Laminae Exist In Vlgn and Dlgnmentioning
confidence: 59%
See 2 more Smart Citations
“…Recent advances in transgenic labeling of individual RGC subtypes has revealed the precise architecture of these hidden laminae of subtype-specific retinal arbors in dLGN (Cruz-Martín et al 2014;Huberman et al 2008;Huberman et al 2009;Kay et al 2011;Kim et al 2010;Kim et al 2008;Martersteck et al 2017;Rivlin-Etzion et al 2011;Kerschensteiner & Guido 2017;Monavarfeshani et al 2017). In this study, however, we identified a different kind of 'hidden laminae' within vLGN.…”
Section: Different Types Of Hidden Laminae Exist In Vlgn and Dlgnmentioning
confidence: 59%
“…In this study, however, we identified a different kind of 'hidden laminae' within vLGN. Notably, the few identified subtypes of vLGN-projecting RGCs do not appear to segregate their terminal arbors into laminae in vLGN (with the notable exception that they are restricted to vLGNe) (Hattar et al 2006;Osterhout et al 2011;Monavarfeshani et al 2017). The diffuse terminal arborization of these non-image forming subtypes of RGCs raises the question of whether visual information is, in fact, parsed into parallel channels in vLGN (Hattar et al 2006;Osterhout et al 2011).…”
Section: Different Types Of Hidden Laminae Exist In Vlgn and Dlgnmentioning
confidence: 99%
See 1 more Smart Citation
“…the dorsal lateral geniculate nucleus [dLGN]) and provide the principle pathway for image-forming visual information to reach the cerebral cortex (Dhande et al, 2015, Seabrook et al, 2017 ( Figure 1A). The recent development of transgenic tools to label these classes of RGCs has revealed that their inputs are segregated into distinct class-specific sublamina within visual thalamus (Huberman et al, 2008, Monavarfeshani et al, 2017, Huberman et al, 2009, Kay et al, 2011, Kim et al, 2008, Kim et al, 2010, Hong and Chen, 2011, supporting the longstanding belief that different features of the visual field are transmitted through the subcortical visual system in parallel, unmixed anatomical channels (Dhande et al, 2015, Cruz-Martín et al, 2014.…”
Section: Introductionmentioning
confidence: 89%
“…before eye-opening) or in vLGN were not affected by the loss of LRRTM1 ( Figure 5A-E,S3B). Since retinal projections account for only a small proportion (5-10%) of all projections innervating relay cells residing in dLGN (Monavarfeshani et al, 2017), we also assessed whether the loss of LRRTM1 altered other types of terminals in dLGN. None of the non-retinal inputs examined appeared affected in lrrtm1 -/mutant mice ( Figure S3C).…”
Section: Lrrtm1 Is Required For the Development Of Complex Rg Synapsesmentioning
confidence: 99%